High-Carbohydrate Diet Alleviates the Oxidative Stress, Inflammation and Apoptosis of Megalobrama amblycephala Following Dietary Exposure to Silver Nanoparticles - Fang Chen; Cai-Yuan Zhao; Jun-Feng Guan; Xiao-Cheng Liu; Xiang-Fei Li; Di-Zhi Xie; Chao Xu (MDPI AG, 2021)
A 12-week feeding trial was performed to evaluate the effects of high-carbohydrate diet on oxidative stress, inflammation and apoptosis induced by silver nanoparticles (Ag-NPs) in M. amblycephala. Fish (20.12 ± 0.85 g) were randomly fed four diets (one control diet (C, 30% carbohydrate), one control diet supplemented with 100 mg kg−1 Ag-NPs (CS), one high-carbohydrate diet (HC, 45% carbohydrate) and one HC diet supplemented with 100 mg kg−1 Ag-NPs (HCS)). The results indicated that weight gain rate (WGR), specific growth rate (SGR), antioxidant enzyme (SOD and CAT) activities and expression of Trx, Cu/Zn-SOD, Mn-SOD, CAT and GPx1 of fish fed CS diet were all remarkably lower than those of other groups, whereas the opposite was true for plasma IL 1β and IL 6 levels, liver ROS contents, hepatocytes apoptotic rate, AMP/ATP ratio, AMPKα, P 53 and caspase 3 protein contents and mRNA levels of AMPKα 1, AMPKα 2, TXNIP, NF-κB, TNFα, IL 1β, IL 6, P 53, Bax and caspase 3. However, high-carbohydrate diet remarkably increased WGR, SGR, liver SOD and CAT activities, AMPKα protein content and mRNA levels of antioxidant genes (Cu/Zn-SOD, Mn-SOD, CAT and GPx1), anti-inflammatory cytokines (IL 10) and anti-apoptotic genes (Bcl 2) of fish facing Ag-NPs compared with the CS group, while the opposite was true for liver ROS contents, hepatocytes apoptotic rate, P 53 and caspase 3 protein contents, as well as mRNA levels of TXNIP, NF-κB, TNFα, IL 1β, IL 6, P 53, Bax and caspase 3. Overall, high-carbohydrate diet could attenuate Ag-NPs-induced hepatic oxidative stress, inflammation and apoptosis of M. amblycephala through AMPK activation.